Measurement of the WW+WZ production cross section using a matrix element technique in lepton+jets events - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We present a measurement of the WW+WZ production cross section observed in a final state consisting of an identified electron or muon, two jets, and missing transverse energy. The measurement is carried out in a data sample corresponding to up to 4.6fb⊃-1 of integrated luminosity at √s=1.96TeV collected by the CDF II detector. Matrix element calculations are used to separate the diboson signal from the large backgrounds. The WW+WZ cross section is measured to be 17.4±3.3pb in agreement with standard model predictions. A fit to the dijet invariant mass spectrum yields a compatible cross section measurement. © 2010 The American Physical Society.